STRATEGI OPTIMALISASI PENDIDIKAN ISLAM DALAM MEMBENTUK KARAKTER ISLAMI PADA MAHASISWA GENERASI Z - Muhalli, Muhalli (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2023)
This study aims to explore and analyze effective Islamic education optimization strategies in shaping Islamic character in generation Z students at the Togo Ambarsari Bondowoso College of Tarbiyah (STIT). Generation Z students, as a group that grew up in the era of globalization technology, have unique educational needs and dynamics. The research method used is a case study, with data collection through in-depth interviews, participatory observation, and document analysis, through this approach, we can deeply understand the experiences and perceptions of generation Z students towards the Islamic education process they receive at STIT Togo Ambarsari Bondowoso as well as the extent to which their Islamic character develops in this context. The results showed that (1) the importance of strategies to optimize Islamic education at STIT Togo Ambarsari Bondowoso includes Islamic value-based, technology in Islamic education, hands-on experience and active learning, the role of social collaboration, the effectiveness of Islamic education strategies; and continuing education in daily life; (2) implications for the development of Islamic education at STIT Togo Ambarsari Bondowoso include the characteristics of generation Z students; relevance of contemporary challenges; recognition of the influence of global culture; challenges and obstacles; Islamic education innovation; and the influence of the campus environment. The results of this study are expected to provide practical guidance for STIT Togo Ambarsari in improving and optimizing Islamic education strategies for generation Z, focusing on important aspects of Islamic character building